The Potency of Sernai (Wedelia biflora) Leaf Water Extract as Antipyretic Compared to Amino Fenol Derivate and Salicylic Acid on Mice (Mus Musculus) - Rinidar Rinidar; Teuku Armansyah; Tesha Aprilya Putri (Universitas Syiah Kuala, 2014)
The study was conducted to screen the antipyretic activity of aqueous of extract of the leaves of sernai (Wedelia biflora) with split-plot design. Eighteen healthy mice weighing between (20-25 g), aged 2-3 months were divided into six groups of three animals each: negative control group were given distilled water (P0), P1, and P2 as a positive control respectively given salicylic acid 42.25 mg/kg body weight, the amino phenol 25 mg/kg body weight, group P3, P4, and P5 given of sernai leaf aqueous extract at a concentration of 50, 75, and 100% respectively. The initial rectal temperature of each animal was recorded by digital thermometer. The pyrexia was induced by injecting a solution of 12.5% peptone. The difference in temperature was observed every 30 minutes for 3 hours and respective time interval was found out by statistical method. The results showed that the water extract of leaves sernai with various concentrations significantly different (P0.01) with an observation time. Average temperatures in the P5 mice was significantly different (P0.05) with P0. P3 and P4 is not significantly different from P0, but P3 and P4 significantly different (P0.05) with P2 and not significantly different from P1. P5 was not significantly different from the P2 and P1 significantly different. It was concluded that the aqueous extract of leaves sernai potential as an antipyretic in mice and at concentrations of 50 and 75% effective in reducing fever in mice tend equivalent to the amino phenol, while the concentration of 100% with salicylic acid.Key words: amino fenol, antipyretic, salicylic acid, sernai